Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-69151
|View full text |Cite
|
Sign up to set email alerts
|

Impeller-Diffuser Interaction in Centrifugal Compressors

Abstract: This paper reports several CFD analyses of a centrifugal compressor stage with a vaned diffuser at high pressure ratio using different techniques to model the rotor-stator interaction. A conventional steady stage calculation with a mixing-plane type interface between the rotor and stator was used as a baseline. This simulation gave excellent agreement with the measured performance characteristics at design speed, demonstrating the ability of the particular steady simulation used to capture the essential featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Optimal radial clearance exists for specific working conditions (Krishnababu, Imregun, Green, & Hoyniak, 2010;Anish & Sitaram, 2009). Robinson, Casey, Hutchinson, and Steed (2012) reported that decreasing the radial clearance ratio substantially increased efficiency. However, when the diffuser was closer to the impeller than the optimum value, the impeller likely experienced mechanical excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal radial clearance exists for specific working conditions (Krishnababu, Imregun, Green, & Hoyniak, 2010;Anish & Sitaram, 2009). Robinson, Casey, Hutchinson, and Steed (2012) reported that decreasing the radial clearance ratio substantially increased efficiency. However, when the diffuser was closer to the impeller than the optimum value, the impeller likely experienced mechanical excitation.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation from the impeller-diffuser interaction is the main excitation acting on the impeller. Because the impeller-diffuser radial gap is becoming smaller by design [13,14], the interaction is getting more intense and the resulting unsteady aerodynamic loads are bigger. Moreover, the five-axis machine is now a common tool for impeller machining and the impeller is machined as one piece with very low structural damping [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Gallier [11] studied excitation mechanisms for impeller-diffuser interaction in a centrifugal compressor. Robinson et al [12] reported the occurrence of mechanical excitation with the impeller when this component was too close to the diffuser.…”
Section: Introductionmentioning
confidence: 99%